In-Situ ‘Divide’ and ‘Deliver’: A Simple Technique to Preserve Nerves in Chimeric Anterolateral Thigh Flap Harvest - Jaiswal, Dushyant; Parekh, Hetanshu; Mathews, Saumya; Ghalme, Amol (Indian Journal of Plastic Surgery, 2023)
Anterolateral thigh (ALT) flap is the workhorse for reconstruction in head and neck post cancer excision. Chimeric multi-paddle flaps are useful for composite defects involving skin, mucosa, and soft tissue. The nerve to vastus lateralis (VL) runs along the pedicle, frequently interdigitating with it or the perforators. Sometimes, the nerve may be preserved during harvest but needs to be sacrificed frequently, leading to increased donor site morbidity.We recommend a simple technique to preserve the nerve, wherein the skin paddles or chimeric components are divided in-situ and manipulated around it without causing injury.This technique was used in 27 cases over 5 years. All involved nerves, perforators and pedicles were preserved.The technique can be extended to any flap harvest with multiple perforators with nerves in proximity, when multiple skin islands are desired.
Keywords: anterolateral thigh flap; technique of alt harvest; free flap reconstruction; donor site morbidity in alt; chimeric alt flap; multiple paddle alt; bipaddle alt harvest